Effect of printing orientation and resin thickness on flexural strength of direct 3D-printed aligners - Ahmed S. Khalil; Abbas R. Zaher (BMC Oral Health, 2025)
Abstract Background Direct 3D-printed aligners served as a breakthrough era in clear aligner fabrication. Yet, there is a scarcity of studies evaluating their mechanical properties. The aim of this study was to compare direct 3D-printed aligners derived from different printing orientations (vertically, horizontally, 30, and 45 degrees) and thickness (0.5 and 0.7 mm) in terms of flexural strength. Methods This laboratory-based comparative study utilized 96 aligner flat specimens. They were designed, supported, and directly printed using shape memory resin, then randomly allocated into 8 groups. Group 1 (A, B, C, and D): 0.5 mm thickness printed vertically, horizontally, 30, and 45 degrees, respectively. Group 2 (A, B, C, and D): 0.7 mm thickness printed vertically, horizontally, 30, and 45 degrees, respectively. Each aligner specimen was placed on a custom-made bending jig, with the whole setup enclosed in a temperature-controlled water bath. Three-point bending test was performed using a universal testing machine, and the resulting force was recorded. Statistical analysis was performed using Student t-test for resin thickness comparison and one-way ANOVA with Tukey post-hoc test for comparison between printing orientations. Statistical significance was set at p ≤ 0.05. Results No statistically significant differences were found between vertically, horizontally, 30, and 45 degrees printed aligner specimens. Aligner specimens of 0.7 mm thickness demonstrated significantly higher flexural strength values compared to those of 0.5 mm thickness. Conclusions Printing orientation did not alter the flexural strength of the direct 3D-printed aligner flat specimens, regardless of whether they were printed vertically, horizontally, or at angles of 30 or 45 degrees relative to the printer build plate. Additionally, specimens with a thickness of 0.7 mm exhibited higher bending resistance compared to those with a thickness of 0.5 mm.